Training on Jarimatika Method for Strengthening Maths Multiplication Count Operation among Children in Sigong Village - Brehnaputrifajar Khaerudin, Rizky; Melani, Atikah; Yani, Ahmad; Fauzan Sidik, Japar; Amilistiyani (Prosiding Seminar Nasional Pengabdian Masyarakat, 2024)
The jarimatika method is a way of counting using fingers to complete arithmetic operations in learning maths easily, quickly and fun. This training was conducted to change children's thinking towards bad judgement in mathematics by providing a method of learning mathematics that is easy to understand and fun. Fourth grade children in Sigong Village were found to still have difficulties in basic multiplication calculations in learning mathematics, especially in counting operations. With the training of the jarimatika method, children can understand mathematics learning that involves counting operations easily and quickly. The purpose of this service activity is to increase interest in learning mathematics so as to make it easier for grade IV children in Sigong Village in basic multiplication counting operations without memorising. To carry out this activity, the lecture and question and answer methods were used. The results of this service are an increase in counting skills in completing basic multiplication calculations and increasing children's interest in learning mathematics in Sigong Village.